الضوابط الشرعية لعمل المرأة في التجارة من المنظور الإسلامي = Shari'a rules for the work of women in trade from Islamic perspective - Ab Razak, Mohamed Rashid; Abbas, Ibrahim (Usuli Faqih Research Centre PLT, 2018)
هذا البحث يهدف إلى إنارة وإبراز مشروعية تجارة المرأة حسب الضوابط الشرعية وأهميتة ذلك باعتباره واقعاً إنسانياً، ذلك أن المرأة كانت تعمل بحسب طبيعتها وما يلائم أحول الناس، والمجتمعات، وإذا كان عمل المرأة وتجارتها له أصل في حضارتنا وفقه شريعتنا، فإنه في هذا العصر ينبغي للمرأة المسلمة أن تسهم في العمل الذي يناسبها، من خلال ذلك سيحاول البحث الإجابة على سؤالين رئيسيين؛ وهما: ما المفهوم بالضوابط الشرعية، وما هي الضوبط الشرعية للتجارة بصفة عامة ولعمل المرأة في التجارة بصفة خاصة؟ كما اتبع البحث المنهج الوصفي التحليلي، وقد توصّل إلى جملة نتائج منها دعوة المرأة المسلمة ليكون لها دور في تنمية المجتمعات المسلمة، وأن لا تتخلى عن التعليم والعمل الذي يخدم الإسلام والأمة وفق معايير الشرع. *************************************************************************************** This study is intended to illuminate and highlight the legality of women's trade according to the rules of Shari'a and the importance of this as a human reality. Women were working according to their nature and what suits the people and communities. If women's work and business have an origin in our civilization and jurisprudence, To contribute to the work that suits them, through which the research will try to answer two main questions: namely, what is the concept of legal controls, and what are the legitimate constraints of trade in general and women's work in trade in particular? The study also followed the analytical descriptive approach, and reached a number of conclusions, including calling on Muslim women to play a role in the development of Muslim societies and not to abandon education and work that serves Islam and the nation according to the Shari'a standards.